Ion—modified optimization of smart scaffolds in bone tissue regeneration - Basavarajappa, Yashas (Frontiers in Biomaterials Science, 2023)
Bioactive glasses and Calcium Phosphate bioceramics have emerged as promising scaffold biomaterials for bone tissue engineering. These materials possess inherent osteoinductive properties that work to create a more suitable environment for bone tissue formation.Additionally, these scaffolds exhibit dissolution properties when submerged in physiological fluids in vivo and therefore can release different ions. Incorporating therapeutic ion-modifiers that have independently demonstrated their osteogenic favorability to these scaffolds can further increase environmental suitability. This review discusses the favorable properties of bioactive glasses and Calcium Phosphate bioceramics in the context of Bone Tissue Engineering as well as potential incorporable metal ion-modifiers.